2014
DOI: 10.1186/1471-2466-14-54
|View full text |Cite
|
Sign up to set email alerts
|

PROLONG: a cluster controlled trial to examine identification of patients with COPD with poor prognosis and implementation of proactive palliative care

Abstract: BackgroundProactive palliative care is not yet common practice for patients with COPD. Important barriers are the identification of patients with a poor prognosis and the organization of proactive palliative care dedicated to the COPD patient. Recently a set of indicators has been developed to identify those patients with COPD hospitalized for an acute exacerbation who are at risk for post-discharge mortality. Only after identification of these patients with poor prognosis a multi disciplinary approach to proa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 50 publications
1
26
0
Order By: Relevance
“…14 Indeed, the Idenitification of Patients with COPD with a Poor Prognosis and Implementation of Proactive Palliative Care (PROLONG) study has been designed to result in better understanding of the effectiveness of proactive palliative care for patients with COPD. 29 Previous studies have reported that patient preferences for end-of-life care are not significantly different between patients with COPD and patients with lung cancer. 13 This suggests that improved and earlier advanced care planning may ensure that end-of-life care for patients with COPD does not exceed their wishes and also curtail health care costs.…”
Section: Discussionmentioning
confidence: 99%
“…14 Indeed, the Idenitification of Patients with COPD with a Poor Prognosis and Implementation of Proactive Palliative Care (PROLONG) study has been designed to result in better understanding of the effectiveness of proactive palliative care for patients with COPD. 29 Previous studies have reported that patient preferences for end-of-life care are not significantly different between patients with COPD and patients with lung cancer. 13 This suggests that improved and earlier advanced care planning may ensure that end-of-life care for patients with COPD does not exceed their wishes and also curtail health care costs.…”
Section: Discussionmentioning
confidence: 99%
“…Data for prognostic accuracy testing in patients hospitalized for an AECOPD were obtained from the PROLONG study 18. This prospective pragmatic cluster controlled trial was performed in six general hospitals in the Netherlands; of those, three were in the intervention condition and three in the control condition.…”
Section: Methodsmentioning
confidence: 99%
“…Usually, COPD patients are very resilient and survive several of these episodes during their lives, including some severe exacerbations – defined as those requiring hospitalization or even ventilator support – until the patient’s death. This uncertain prognosis complicates matters for clinicians unfamiliar with PC in initiating discussions about PC and end-of-life care planning 6. Although many variables have demonstrated a close relationship with impaired survival in COPD, their utility for evaluating survival in an individual patient in the short or medium term is debatable, and therefore, their usefulness as main criteria to initiate PC is not well established.…”
Section: Introductionmentioning
confidence: 99%